Improved photocatalytic performance of TiO2/carbon photocatalysts: Role of carbon additive - Abreu-Jaureguí, Coset; Andronic, Luminita; Sepúlveda-Escribano, Antonio; Silvestre-Albero, Joaquín (Elsevier B.V., 2024)
A series of TiO2 – based photocatalysts have been prepared by the incorporation of 10 wt% of various carbon-based nanomaterials as modifying agents to titania. More specifically, commercial TiO2 P25 was modified through a wet impregnation approach with methanol with four different carbon nanostructures: single-walled carbon nanotubes (SWCNTs), partially reduced graphene oxide (prGO), graphite (GI), and graphitic carbon nitride (gCN). Characterization results (XPS and Raman) anticipate the occurrence of important interfacial phenomena, preferentially for samples TiO2/SWCNT and TiO2/prGO, with a binding energy displacement in the Ti 2p contribution of 1.35 eV and 1.54 eV, respectively. These findings could be associated with an improved electron-hole mobility at the carbon/oxide interface. Importantly, these two samples constitute the most promising photocatalysts for Rhodamine B (RhB) photodegradation, with nearly 100% conversion in less than 2 h. These promising results must be associated with intrinsic physicochemical changes at the formed heterojunction structure and the potential dual-role of the composites able to adsorb and degrade RhB simultaneously. Cyclability tests confirm the improved performance of the composites (e.g., TiO2/SWCNT, 100% degradation in 1 h) due to the combined adsorption/degradation ability, although the regeneration after several cycles is not complete due to partial blocking of the inner cavities in the carbon nanotubes by non-reacted RhB. Under these reaction conditions, Rhodamine-B xanthene dye degrades via the de-ethylation route.
Keywords: Photocatalysis; Oxide/carbon; Interfacial phenomena; Rhodamine B